Estimating gold-ore mineralization potential within Topolninsk ore field (Gorny Altai) - Timkin, Timothy Vasilyevich; Voroshilov, Valery Gavrilovich; Асканакова Ольга Юрьевна; Cherkasova, Tamara Yurievna; Chernyshov, A.; Korotchenko, Tatiana Valerievna (IOP Publishing, 2015)
Based on the results of ore and near-ore metasomatite composition analysis, the factors and indicators of gold-ore mineralization potential were proposed. Integration of the obtained data made it possible to outline magmatic, structural, and lithological factors, as well as direct and indirect indicators of gold-ore mineralization. Applying multidimensional analysis inherent to geochemical data, the spatial structure was investigated, as well as the potential mineralization was identified. Based on the developed and newly-identified mineralization, small (up to medium-sized) mineable gold-ore deposits in skarns characterized by complex geological setting was identified.
Keywords: Золото; минерализация; рудные поля; Горный Алтай; метасоматиты; золоторудная минерализация; геохимические данные